L'Oreal - Hisrich, Robert D.; Kearney, Claudine ([London] : SAGE, 2016)
This case describes the creation and global expansion of L'Oreal, the leading perfumes and cosmetics manufacturer. It presents a historical overview on the growing business model of the company and the partnerships and acquisitions that have fueled its growth throughout the years.
Originally Published in: Hisrich, R. D., & Kearney, C. (2013). Scenario: L'Oreal. In Managing innovation and entrepreneurship (pp. 83-87). Los Angeles: SAGE Publications, Inc. ISBN: 9781452241357.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; L'Oreal (Firm); Consolidation and merger of corporations -- Case studies